Regional Low-Emission Pathways from Global Models - Heleen van Soest; Lara Aleluia Reis; Detlef van Vuuren; Christoph Bertram; Laurent Drouet; Jessica Jewell; Elmar Kriegler; Gunnar Luderer; Keywan Riahi; Joeri Rogelj; Massimo Tavoni; Michel den Elzen; et al. (Fondazione Eni Enrico Mattei (FEEM), 2015)
Governments worldwide have agreed that international climate policy should aim to limit the increase of global mean temperature to less than 2oC with respect to pre-industrial levels. The purpose of this paper is to analyse the emission reductions and related energy system changes in various countries in pathways consistent with the 2oC target. We synthesize and provide an overview of the national and regional information contained in different scenarios from various global models published over the last few years, as well as yet unpublished scenarios submitted by modelling teams participating in the MILES project (Modelling and Informing Low-Emission Strategies). We find that emissions in the mitigation scenarios are significantly reduced in all regions compared to the baseline without climate policies. The regional cumulative CO2 emissions show on average a 76% reduction between the baseline and 450 scenario. The 450 scenarios show a reduction of primary energy demand in all countries of roughly 30-40% compared to the baseline. In the baseline scenario, the contribution of low-carbon energy technology remains around 15%, i.e. similar as today. In the mitigation scenario, these numbers are scaled up rapidly towards 2050. Looking at air quality, sulphur dioxide and black carbon emissions are strongly reduced as a co-benefit of greenhouse gas emission reductions, in both developing and developed countries. However, black carbon emissions increase in countries that strongly rely on bioenergy to reach mitigation targets. Concerning energy security, energy importing countries generally experience a decrease in net-energy imports in mitigation scenarios compared to the baseline development, while energy exporters experience a loss of energy export revenues.
Keywords: Q54; 330; Climate policy; Mitigation; Global and national policy comparison